2021
DOI: 10.1016/j.molmet.2021.101259
|View full text |Cite
|
Sign up to set email alerts
|

Direct small molecule ADaM-site AMPK activators reveal an AMPKγ3-independent mechanism for blood glucose lowering

Abstract: Objective Skeletal muscle is an attractive target for blood glucose-lowering pharmacological interventions. Oral dosing of small molecule direct pan-activators of AMPK that bind to the allosteric drug and metabolite (ADaM) site, lowers blood glucose through effects in skeletal muscle. The molecular mechanisms responsible for this effect are not described in detail. This study aimed to illuminate the mechanisms by which ADaM-site activators of AMPK increase glucose uptake in skeletal muscle. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This is probably because of the distal part of the PKR and AMPKβ (Snf4 in S . cerevisiae ) forming the (allosteric drug and metabolite) ADaM pocket ( Calabrese et al., 2014 ; Jørgensen et al., 2021 ). This pocket centered around G53 may also explain why the hyperactive Sc Snf1 G53R mutant suppresses snf4 ( Estruch et al., 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because of the distal part of the PKR and AMPKβ (Snf4 in S . cerevisiae ) forming the (allosteric drug and metabolite) ADaM pocket ( Calabrese et al., 2014 ; Jørgensen et al., 2021 ). This pocket centered around G53 may also explain why the hyperactive Sc Snf1 G53R mutant suppresses snf4 ( Estruch et al., 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMPKγ3 ( PRKAG3 ) knockout (KO) mice were generated at The Jackson Laboratory (Bar Harbor, ME) using clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 technology as previously described ( 11 ). In short, Cas9 protein with a single guide RNA was used to induce a frameshift deletion in exon 6, resulting in a premature truncation of the PRKAG3 gene and KO of the AMPKγ3 protein.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological activation of AMPK in skeletal muscle increases glucose uptake ( 7 , 8 ), and observations from rodent models and nonhuman primates have confirmed that targeting AMPK in skeletal muscle by selective activators is a viable therapeutic approach to reverse hyperglycemia ( 9 , 10 ). We and others have shown that ADaM-site–binding small-molecule activators of AMPK, including PF739, 991, and MK-8722, increase muscle glucose uptake via an AMPKα-dependent but AMPKγ3-independent mechanism ( 11 , 12 ). In contrast, the nonspecific AMPK activator AICAR (AMP mimetic) has repeatedly been shown to increase muscle glucose uptake via an AMPKγ3-dependent mechanism ( 11 13 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent in vivo studies have shown that MK-8722, PF-739 and 991 induced skeletal muscle glucose uptake independently of α2β2γ3 [29,30]. This important finding, combined with our previous report showing β2-dependent increases in ex vivo glucose uptake in mouse soleus and extensor digitorum longus (EDL) muscles by the imidazopyridine SC4, implicate α2β2γ1 complexes as the physiological target for ADaM site drugs in skeletal muscle [21,29,30]. Furthermore, SC4 activates all six α2 complexes in vitro but demonstrates poor activation potential against α1β2γ1.…”
Section: Introductionmentioning
confidence: 99%